Disruption of a new X linked gene highly expressed in brain in a family with two mentally retarded males. Issue 10 (1st October 2004) - Cantagrel, V; Lossi, A-M; Boulanger, S; Depetris, D; Mattei, M-G; Gecz, J; Schwartz, C E; Van Maldergem, L; Villard, L
Abstract : Background: Mental retardation (MR) affects 2–3% of the human population and some of these cases are genetically determined. Although several genes responsible for MR have been identified, many cases have still not been explained. Methods: We have identified a pericentric inversion of the X chromosome inv(X)(p22.3;q13.2) segregating in a family where two male carriers have severe MR while female carriers are not affected. Results: The molecular characterisation of this inversion led us to identify two new genes which are disrupted by the breakpoints: KIAA2022 in Xq13.2 and P2RY8 in Xp22.3. These genes were not previously fully characterised in humans. KIAA2022 encodes a protein which lacks significant homology to any other known protein and is highly expressed in the brain. P2RY8 is a member of the purine nucleotide G-protein coupled receptor gene family. It is located in the pseudo-autosomal region of the X chromosome and is not expressed in brain. Conclusions: Because the haploinsufficiency of P2RY8 in carrier mothers does not have a phenotypic consequence, we propose that the severe MR of the affected males in this family is due to the absence of the KIAA2022 gene product. However, screening 20 probands from X linked MR families did not reveal mutations in KIAA2022. Nonetheless, the high expression of this gene in fetal brain and in the adult cerebral cortex could be consistent with a role in brain development and/or cognitive function.